Association of Academic Stress with Cortisol Levels and Oxidative Stress Markers in Medical Students - Akram, Sana; Munir, Khurram; Khaliq, Shagufta; Junaid, Shazia; Munir, Hina; Afridi, Saleha (Journal of Neonatal Surgery, 2025)
Background: Academic stress is increasingly recognized as a significant public health issue among medical students, influencing both psychological well-being and physiological balance. Activation of the hypothalamic–pituitary–adrenal (HPA) axis during stress elevates cortisol levels, potentially leading to oxidative stress through disruption of redox homeostasis. Objective: To determine the association between academic stress, serum cortisol levels, and oxidative stress markers among undergraduate medical students. Methods: A cross-sectional analytical study was conducted on 150 medical students. Academic stress was measured using the Perceived Stress Scale (PSS). Serum cortisol was assessed via ELISA, while oxidative stress markers, malondialdehyde (MDA), total oxidant status (TOS), and total antioxidant capacity (TAC) were measured using standardized biochemical assays. Data were analyzed using SPSS version 25. Pearson correlation, independent t-test, and multivariate regression analysis were applied, with p < 0.05 considered statistically significant. Results: The mean PSS score was 21.8 ± 5.6, indicating moderate to high stress. High-stress students exhibited significantly higher cortisol levels (18.6 ± 4.2 µg/dL) compared to low-stress students (11.9 ± 3.5 µg/dL, p < 0.001). MDA and TOS levels were significantly elevated, while TAC was reduced in the high-stress group (p < 0.001). Cortisol showed strong positive correlations with MDA (r = 0.62) and TOS (r = 0.58), and a negative correlation with TAC (r = −0.49). Conclusion: Academic stress is significantly associated with elevated cortisol and oxidative stress in medical students. Institutional interventions targeting stress reduction are essential to improve student health outcomes.